2013
DOI: 10.1371/journal.pgen.1003714
|View full text |Cite
|
Sign up to set email alerts
|

A Shift to Organismal Stress Resistance in Programmed Cell Death Mutants

Abstract: Animals have many ways of protecting themselves against stress; for example, they can induce animal-wide, stress-protective pathways and they can kill damaged cells via apoptosis. We have discovered an unexpected regulatory relationship between these two types of stress responses. We find that C. elegans mutations blocking the normal course of programmed cell death and clearance confer animal-wide resistance to a specific set of environmental stressors; namely, ER, heat and osmotic stress. Remarkably, this pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 82 publications
1
33
0
1
Order By: Relevance
“…However, a role for molecular damage in age-related pathology in the gonad cannot be ruled out. Consistent with the latter possibility, mutation of ced-3 increases resistance to several stressors, particularly ER stress [31]. Also, molecular damage could contribute to age decline in GP rate.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, a role for molecular damage in age-related pathology in the gonad cannot be ruled out. Consistent with the latter possibility, mutation of ced-3 increases resistance to several stressors, particularly ER stress [31]. Also, molecular damage could contribute to age decline in GP rate.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies suggest not: for example, lifespan was not extended either by blocking uterine tumor growth [19] or blocking apoptosis using ced-3(n1286) [20]. However, several studies have reported increases in lifespan resulting from loss of ced-3 function, either using ced-3(n717) [31], like ced-3(n1286) a strong allele [32], or ced-3 RNAi initiated at L4 [33], which suppresses only germline apoptosis. We tested both interventions, but no increase in lifespan was seen (Supplementary Figure 6A, 6B, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Moreover, pgrn-1 mutants have been reported to be refractory to ER stress-induced apoptosis measured by resistance to tunicamycin, an inhibitor of N-linked glycosylation. 24 Collectively, these findings indicate the possibility that ER stress may contribute to the regulatory role of PGRN on insulin resistance and metabolic dysfunction.…”
Section: Introductionmentioning
confidence: 92%
“…Classic cell death machinery have important non-apoptotic functions including muscle development in mammals (Fernando et al, 2002), neuronal regeneration in C. elegans (Pinan-Lucarre et al, 2012), control of longevity in C. elegans (Yee et al, 2014), stress-responsiveness in C. elegans (Judy et al, 2013), and control of stemness in mammals and C. elegans (Fujita et al, 2008; Weaver et al, 2014). Non-apoptotic caspase activity, with as-yet unknown function, has also been observed using caspase-sensitive cellular reporters in Drosophila (Tang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%